The effect of seminal plasma cadmium and lead levels on semen parameters in male subjects of infertile couples: a prospective cohort study - Tuncay, Gorkem; Karaer, Abdullah; Tanrikut, Emrullah; Ozgul, Onur (Journal of obstetrics and gynaecology, 2021)
The aim of this prospective study was to investigate whether there is a relationship between seminal plasma cadmium (Cd) and lead (Pb) levels and semen parameters in male partners of infertile couples. Two hundred fifty one (251) men recruited with no history of occupational exposure to toxic metals. After semen analysis, seminal Cd and Pb levels were measured using atomic absorption spectrometry. Cadmium levels in men with hypospermia was significantly higher than men with normal semen volume ( = .049). In contrast, there was no statistically significant difference in median seminal Pb levels between men with hypospermia and men with normal semen volume ( = .13). There was no statistically significant association between seminal plasma Cd and Pb levels sperm concentration, motility, morphology and total progressively motile sperm count. These findings suggest that environmental Cd exposure may contribute to low semen volume in male partners of infertile couples.IMPACT STATEMENT Toxic metals may adversely affect both male and female reproductive system. Seminal plasma cadmium levels in men with hypospermia were statistically significantly higher than men with normal semen volume. Patients should be informed about possible adverse effects of toxic metals.